Analisis Korean Wave terhadap Purchase Intention Produk Lokal Somethinc dengan Customer Trust sebagai Mediasi (Survei pada Mahasiswa di Kota Sukabumi) - Bintan Nursalimah; Asep Muhamad Ramdan; Resa Nurmala (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The increasing influence of the Korean Wave (Hallyu) has reshaped consumer behavior in Indonesia, particularly in the skincare industry. Although local brands such as Somethinc have adopted K-Beauty concepts and Korean cultural elements, consumer trust toward local products remains relatively lower than toward Korean brands, resulting in inconsistent purchase intention. This study aims to examine the effect of the Korean Wave on purchase intention for Somethinc skincare products, with customer trust as a mediating variable. A quantitative approach with a causal associative design was employed. Data were collected through an online questionnaire using a semantic differential scale (1–7) from 150 university students in Sukabumi City, selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that the Korean Wave has a positive and significant effect on purchase intention. Customer trust also significantly influences purchase intention and partially mediates the relationship between the Korean Wave and purchase intention. Although the direct effect of the Korean Wave is stronger, customer trust plays a crucial role in reinforcing consumers’ intention to purchase local skincare products. These findings suggest that integrating Korean cultural elements with strategies to strengthen consumer trust can enhance the competitiveness of local skincare brands.